Rhabdomyosarcoma Requiring Ovarian Transposition Release for Recurrent Severe Ovulation Pain Following Laparoscopic Ovarian Transposition: A Case Report - Yuko Shimoji; Keiko Mekaru; Akiko Ikemura; Natsuki Tamashiro; Shuko Chinen; Rie Nakamura; Chiaki Heshiki; Wataru Kudaka; Masayuki Sekine (Reproductive Medicine and Biology)
ABSTRACT Case Ovarian transposition (OT) is performed to preserve ovarian function in patients undergoing pelvic or abdominal radiotherapy. Although complications, such as ovarian torsion and cyst formation, have been reported, ovulation‐related peritoneal irritation requiring surgical intervention after pediatric OT has not been documented. In this case, a 12‐year‐old girl who underwent bilateral OT at the age of 6 years during treatment for recurrent rhabdomyosarcoma presented with severe pain in the right lower quadrant. Owing to prior pelvic radiotherapy, the assessment of menstrual history was unreliable. Considering the young age of the patient and the absence of a definitive diagnosis, hormonal therapy, such as low‐dose estrogen–progestin therapy, was withheld. Conservative management with analgesics was initiated; however, the pain persisted and progressively worsened. Outcome Emergent laparoscopic OT release was performed for diagnostic and therapeutic purposes, owing to the severity of pain. Intraoperative findings revealed corpus luteum in the retracted right ovary. Postoperatively, the patient's symptoms resolved immediately without recurrence. Conclusion Ovulation‐induced peritoneal irritation should be recognized as a potential postoperative complication following childhood OT. In adolescent patients with a history of pediatric OT and pelvic radiotherapy, ovulation‐related complications should be carefully considered during the differential diagnosis of acute abdominal pain.